Development of a health index for stranded marine tetrapods - André S. Barreto; Karla R. K. Andrioli; Ana Paula F. R. L. Bracarense; Marta J. Cremer; Daphne W. Goldberg; Guilherme Guerra-Neto (PLoS ONE, 2025)
This study presents the development and validation of a Health Index (HI) to assess the overall health of stranded marine tetrapods (seabirds, sea turtles, and marine mammals). The HI is based on parameters collected during necropsies and histopathological analyses, including body condition, systemic conditions (macroscopic and by histopathology), cutaneous injuries, organized lesions, parasitosis, lymphoid depletion, and thyroid alterations. The HI was applied to data from 6,332 marine tetrapods stranded along the Brazilian coast. Results showed that the HI effectively differentiated between animals with good, fair, and poor health, as evaluated by independent veterinary assessments. Sea turtles exhibited the lowest average HI, suggesting poorer health conditions compared to seabirds and marine mammals. The HI has proven to be a valuable tool for monitoring the health of marine tetrapod populations. Using a quantitative measure of an animal’s health enables the evaluation of spatial and temporal variations in health status and the identification of more subtle impacts on species or populations. Thus, the HI allows for an objective assessment and comparison of wildlife health, supporting conservation efforts and helping to identify potential threats.